Kinerja Petani Dalam Program Pertanian Organik Gabungan Kelompok Tani (Gapoktan) Di Desa Cibuah Kecamatan Warunggunung Kabupaten Lebak Banten - Herdi Budiharto; Sholih Sholih; Ino S Rawita (Universitas Maritim AMNI Semarang, 2023)
This research aims to describe the performance of farmers in the Combined Farmer Group Organic Agriculture Program (GAPOKTAN) in Desa Cibuah Kecamatan Warunggunung Kabupaten Lebak Banten. The approach used is a qualitative approach using descriptive methods. Data was obtained using observation, interview and documentation study data collection techniques. The informants in this research were the chairman of the Sari Tani agricultural group, the Sari Tani agricultural secretary, and members of the Sari Tani agricultural group. The research results show that the performance of farmers in organic farming programs tends to increase. The productivity of organic crops such as rice, vegetables and fruit has increased significantly. Additionally, farmers also report improvements in natural resource and environmental management, reflecting a commitment to sustainable agricultural practices. Trust between farmers in farmer groups creates a harmonious work environment and supports the exchange of resources and social support. In this research, challenges such as limited resources and climate change remain obstacles to the sustainability of this program. Therefore, this research recommends the need for further support from the government and related parties to increase farmers' access to resources and technology that support organic farming as well as strengthening social capital in the form of training and coaching farmer groups.